Comparison water quality in Seri Mendapat area and Merlimau area (Elaeis guineensis) / Mohamad Shah Jehan Mohamad Hisham - Mohamad Hisham, Mohamad Shah Jehan (Faculty of Plantation and Agrotechnology, 2019)
Water quality is important for oil palm plantation. It is because water quality have component such as water salinity and water pH in water structures. The water salinity and water pH is important for plantation to give the yield. Because when the plant is up take good water quality give the good feedback from plant. The study was conducted to compare the mean of water pH, water salinity (Nacl) and total dissolved solids (TDS). The area of study is Kampung Seri Mendapat area and Merlimau area. The crop focus is oil plant plantation (elaeis guineensis). 10 sample water are collected every week. The samples are collected at same point every week and have 4 replication. The samples were taken from Kampung Seri Mendapat area and other samples from Merlimau area. Cyberscan PCD 650 was used for measures the water quality such as water pH, water ion and conductivity, total dissolved solids water, water salinity, water resistivity, dissolved, water oxygen and water temperature The average mean of water pH for Kampung Seri Mendapat area is 3.45 and Merlimau is 3.86. The level of pH for the both area is acidic average water salinity in Kampung Seri Mendapat area is 438.94 ppm and merlimau is 354.97 ppm. For the Merlimau water salinity level is low while in Seri Mendapat is moderately salinity level. Total Dissolved Solids mean in Kampung Seri Mendapat area is 442.20 ppm and Merlimau is 358.24 ppm. For TDS Seri Mendapat is good condition and the excellent condition for Merlimau area.